Nutrition Interventions for the Most Vulnerable and Access to Humanitarian Supplies : Progress and Prospects - World Bank (World Bank, Washington, DC, 2013)
This report relates to the food security pillar of the declaration on Development by G20 Leaders of the G20 Seoul Summit. It responds to a request from Brazil, Canada, France and Japan (co-facilitators on Food Security), on behalf of the co-chairs of the G20 Development Working Group. It contributes to Food Security Pillar Action 2 - the mitigation of risk associated with food insecurity and price volatility, and enhancement of protection for the most vulnerable. It focuses on enhancing human and social capital within communities at risk through a) ensuring access to humanitarian supplies and b) addressing the nutritional needs of the most vulnerable. It complements reports produced by others working on food security, including Price volatility in food and agricultural markets: Policy Responses prepared by nine international organizations under the coordination of FAO and OECD.